A multicenter study on TROP2 as a potential targeted therapy for extramammary Paget disease in Japan - Takamichi Ito; Yuka Tanaka; Dai Ogata; Haruto Nishida; Tatsushi Shiomi; Ryo Tanaka; Aya Kawaguchi; Azusa Miyashita; Satoshi Fukushima; Naoko Shojiguchi; Hiroyuki Goto; Yaei Togawa; et al. (Scientific Reports)
Abstract Extramammary Paget disease (EMPD) is a rare skin cancer that typically occurs in the anogenital area of older people. Since efficacy of treatments for metastatic or unresectable EMPD remains poor, development of a novel therapeutic approach is strongly desired. However, the lack of EMPD models has hampered investigation of EMPD. Here we investigated whether trophoblast cell surface antigen 2 (TROP2) could be a promising therapeutic target for EMPD. We retrospectively collected 108 samples from 54 patients with primary and metastatic EMPD from 10 Japanese institutions, and compared TROP2 expression between primary and metastatic lesions of each paired sample. In vitro assays were performed using a newly established EMPD cell line, KS-EMPD-1. TROP2 was strongly and homogeneously expressed in patient tissues, regardless of primary or metastatic lesions. The KS-EMPD-1 cells were treated with a TROP2-targeted antibody–drug conjugate (ADC), sacituzumab govitecan, and it significantly reduced cell viability in a dose-dependent manner compared with that of the cells treated with sacituzumab alone. Knockdown of TROP2 reduced cell viability and cell migration, and caused slight upregulation of the apoptosis-related factors, together with downregulation of the epithelial-to-mesenchymal transition-related factors. These findings suggest that a TROP2-targeted ADC may be a promising treatment option for unresectable EMPD.